Validation of educational technology for the prevention and control of contact-borne infections - Natália Pimentel Gomes Souza; Paulo César de Almeida; Rhanna Emanuela Fontenele Lima de Carvalho; Maria Lúcia Duarte Pereira (Rev Rene)
Objective: to build and validate the content and appearance of the booklet on prevention and control of contact-borne infections. Methods: methodological study, developed from the validation of an educational booklet by expert judges and by the target audience. The validation was performed by seventeen judges from different Brazilian regions and seven companions. The agreement index between the evaluators was calculated, with a minimum of 80.0% being necessary to guarantee the validation of the material. Results: most of the items obtained agreement rates above the recommended. The changes were made according to the judges’ suggestions, giving rise to the second version of the booklet, which was submitted to the appearance validation by the target audience, culminating in changes in the cover and language. Conclusion: the booklet was considered valid by specialists and by the target audience, and could be technology used for companions of patients kept in contact isolation.